Kniest dysplasia in girl aged 4 years: a case report - Sahoo, Ipsita; Jena, Nitish; Dash, Mrutunjay; Bisoi, Swarup (Indonesian Pediatric Society, 2024)
Kniest dysplasia is a rare chondrodysplasia characterized by distinct musculoskeletal and craniofacial abnormalities. Additional features like hearing loss and some ocular abnormalities can also be present. We report a case of Kniest dysplasia from eastern India with a rare mutation confirmed by genetic testing. A 4-year-old girl presented with skeletal deformities with normal intelligence. On examination, she had dysmorphism, short stature, barrel-shaped chest, scoliosis, short limbs with enlarged joints, and dental problems. The skeletal survey showed platyspondyly, epiphyseal enlargement, and a hypoplastic femoral head with cloud-like calcification. Clinical suspicion of Kniest dysplasia was kept based on characteristic skeletal abnormalities and radiological findings. The diagnosis was confirmed by genetic analysis, which revealed a mutation in the COL2A1 gene (c.905C>T) on chromosome 12 exon 14.